Extraovarian granulosa cell tumor - Paul Prabir; Chakraborty Jayati; Chakrabarti Sudipta; Chattopadhyay Bitan (Wolters Kluwer Medknow Publications, 2009)
Extraovarian granulosa cell tumor (GCT) is a very uncommon tumor, assumed to arise from the ectopic gonadal tissue along the embryonal route of the genital ridge. One such rare case of extraovarian GCT was encountered in a 58-year-old female who presented with a large intraabdominal lump. Computerized tomography revealed one large retroperitoneal mass measuring 15cm x 16cm and another mesenteric mass of 8cm x 5cm size. The patient had a history of hysterectomy with bilateral salpingooophorectomy 20 years ago for uterine leiomyoma. Ultrasonography-guided aspiration smears revealed cytological features suggestive of GCT. Histopathological examination of the excised masses showed features of adult-type GCT. Because metastatic epithelial tumors, particularly from the ovaries, may show identical morphology, immunostains for inhibin and epithelial membrane antigen (EMA) were performed. The tumor showed positivity for inhibin while EMA was negative thus confirming the diagnosis of GCT. As this patient had no previous history of GCT and was oophorectomized 20 years ago, the tumor was considered as extraovarian. A diagnosis of extraovarian GCT should be carried out after excluding any previous history of GCT of the ovary. Immunostains help to differentiate GCTs from other neoplasms.